2018
DOI: 10.1002/cne.24537
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the claustrum and endopiriform nucleus: A perspective towards consensus on cross‐species homology

Abstract: With the emergence of interest in studying the claustrum, a recent special issue of the Journal of Comparative Neurology dedicated to the claustrum (Volume 525, Issue 6, pp. 1313-1513) brought to light questions concerning the relationship between the claustrum (CLA) and a region immediately ventral known as the endopiriform nucleus (En). These structures have been identified as separate entities in rodents but appear as a single continuous structure in primates. During the recent Society for Claustrum Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
118
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 79 publications
(127 citation statements)
references
References 189 publications
(325 reference statements)
8
118
1
Order By: Relevance
“…The nucleus endopiriformis as that brain structure with the highest density of GFP pos neurons was identified by three different approaches: (a) anatomical comparison with the corresponding coronal, sagittal, and horizontal sections of a stereotactic atlas of the mouse brain (Franklin & Paxinos, ), (b) analysis of PV expression pattern in the claustrum and endopiriform nucleus, and (c) by analysis of projections from the cingulate cortex to the nucleus endopiriformis or claustrum via DiI labeling. In agreement with previous reports (Kim, Matney, Roth, & Brown, ; Real et al, ; Smith et al, ; Wójcik et al, ), we only found scarce PV immunoreactivity in the area with the highest density of GFP pos neurons, supporting our finding that GFP pos neurons are located within the nucleus endopiriformis. Moreover, analysis of DiI labeling of cingulate cortex projection neurons revealed DiI‐positive fibers in close vicinity to GFP pos EPP neurons.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The nucleus endopiriformis as that brain structure with the highest density of GFP pos neurons was identified by three different approaches: (a) anatomical comparison with the corresponding coronal, sagittal, and horizontal sections of a stereotactic atlas of the mouse brain (Franklin & Paxinos, ), (b) analysis of PV expression pattern in the claustrum and endopiriform nucleus, and (c) by analysis of projections from the cingulate cortex to the nucleus endopiriformis or claustrum via DiI labeling. In agreement with previous reports (Kim, Matney, Roth, & Brown, ; Real et al, ; Smith et al, ; Wójcik et al, ), we only found scarce PV immunoreactivity in the area with the highest density of GFP pos neurons, supporting our finding that GFP pos neurons are located within the nucleus endopiriformis. Moreover, analysis of DiI labeling of cingulate cortex projection neurons revealed DiI‐positive fibers in close vicinity to GFP pos EPP neurons.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, analysis of DiI labeling of cingulate cortex projection neurons revealed DiI‐positive fibers in close vicinity to GFP pos EPP neurons. Strong connectivity between the cingulate cortex and the claustrum–endopiriform complex was reported previously (Behan & Haberly, ; Condé et al, ; Qadir et al, ; Smith et al, ; Wang et al, ; Watson et al, ; White et al, ; Zingg et al, ), confirming our observations that these GFP pos neurons are located within the endopiriform nucleus. The endopiriform nucleus is strongly connected to the amygdaloid complex, therefore retrograde labeling of amygdalar projection neurons could further corroborate our finding that GFP pos neurons are located within the endopiriform nucleus (Majak et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations